Biosynthesis of Di-myo-Inositol-1,1′-Phosphate, a Novel Osmolyte in Hyperthermophilic Archaea - Chen, Liangjing (American Society for Microbiology, 1998)
Biosynthesis of di-myo-inositol-1,1′-phosphate (DIP) is proposed to occur with myo-inositol and myo-inositol 1-phosphate (I-1-P) used as precursors. Activation of the I-1-P with CTP and condensation of the resultant CDP-inositol (CDP-I) with myo-inositol then generates DIP. The sole known biosynthetic pathway of inositol in all organisms is the conversion of d-glucose-6-phosphate to myo-inositol. This conversion requires two key enzymes: l-I-1-P synthase and I-1-P phosphatase. Enzymatic assays using (31)P nuclear magnetic resonance spectroscopy as well as a colorimetric assay for inorganic phosphate have confirmed the occurrence of l-I-1-P synthase and a moderately specific I-1-P phosphatase. The enzymatic reaction that couples CDP-I with myo-inositol to generate DIP has also been detected in Methanococcus igneus. (13)C labeling studies with [2,3-(13)C]pyruvate and [3-(13)C]pyruvate were used to examine this pathway in M. igneus. Label distribution in DIP was consistent with inositol units formed from glucose-6-phosphate, but the label in the glucose moiety was scrambled via transketolase and transaldolase activities of the pentose phosphate pathway.